CHANGES IN LAND COVER AND TOTAL AREA OF MANGROVE DAMAGE FOR 10 YEARS FROM 2012 TO 2022 IN BUNATI VILLAGE, ANGSANA DISTRICT, TANAH BUMBU REGENCY - IRA PUSPITA DEWI; NURSALAM; SITI FATIMAH (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
Mangrove is a forest that grows on the coast, generally found in protected estuaries, river banks, and lagoons in subtropical and tropical regions. Mangroves describe ecosystems and plant families that can adapt to an environment influenced by tides. The condition of the mangroves in Bunati Village is quite apprehensive due to the conversion of mangrove land to other land uses such as oil palm plantations, industrial mining excavations, and others, seen from Google Earth images for 2013 and 2022, causing mangrove land cover in Bunati Village to decrease. Therefore it is necessary to analyze changes in land cover and the total area of mangrove damage for ten years from 2012 to 2022 in Bunati Village, Angsana District, Tanah Bumbu Regency, South Kalimantan Province. This study uses Sentinel 2 Satellite Image data for 2022, SPOT 7 for 2017, and SPOT 4 for 2012. The data analysis carried out is overlay. Changes in land cover in 2012 and 2022 in Bunati Village, namely mangrove land remaining to become mangroves covering an area of 73.48 hectares with a percentage of 39.88%, mangroves to non-mangrove 108.99 hectares with a percentage of 59.00%, mangroves to waters 2.05 hectares with a percentage of 1.12%, non-mangrove to mangrove 29.84 hectares with a percentage of 2.81%, non-mangrove to remain non-mangrove 1029.27 hectares with a percentage of 97.02%, non-mangrove to waters 1.79 hectares with a percentage 0.17%, waters turned into mangroves 6.67 hectares with a percentage of 47.14%, waters turned non-mangrove 5.43 hectares with a percentage of 38.35%, and waters turned into waters 2.21 hectares with a percentage of 14.51%. The total area of mangroves that have suffered damage or shrinkage is 74.74 hectares.